Adolf Hitler : Volume 1 - Toland, John. (Garden City, N.Y. : Doubleday, 1976)
Here is a monumental, vastly revealing biography of Adolf Hitler - filled with brilliant, original insights into the familiar aspects of Hitler's and offering a wealth of new material only recently discovered and never published.
Includes index.
Bibliography: p. [906]-923.
Keywords: Hitler, Adolf, -- 1889-1945.; Heads of state -- Germany -- Biography; Germany -- History -- 1933-1945.